REDIC: Recomendação de Influenciadores Digitais do Queijo Artesanal Brasileiro - Soares, Nedson Donato; Braga, Regina; David, José Maria N.; Siqueira, Kennya Beatriz; Nogueira, Thallys da Silva; Campos, Emerson Wendelin; Moraes, Emerson Augusto Priamo; Goliatt, Priscila Vanessa Zabala Capriles (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2021)
The advancement of information technology makes social media networks increasingly gain popularity and insertion in daily life aspects. Thus, the analysis of people's opinions and habits is essential for many companies' modernization and survival. On social networks, people generally share their views and visit other people's opinions about products, news, and trends, and the concept of "influential person" emerges. An influential person (or social media influencer) today is considered a marketing strategy. The Brazilian dairy industry has been standing out every year, and one of the promising areas is cheese production. The 2019 annual report by ABLV (Associação Brasileira da Indústria de Lácteos Longa Vida) indicates that there was an increase of 32% in liters of milk destined for cheese production in Brazil compared to 2009, which is greater than the percentage growth of milk UHT (26%). Intending to collect information from social networks to find influential people, who appreciate artisanal cheeses, and who can influence potential new consumers, this work presents REDIC, a proposal for analysis, recommendation, and content propagation network, considering the Brazilian artisanal cheese market. REDIC classifies the user's content and interactions using ontologies and complex networks, deriving new relationships and allowing interconnecting information on different social networks. REDIC was developed to support the market research of artisanal cheeses in a renowned Brazilian agribusiness institution. The results obtained through feasibility studies showed that the solution allows the search for communities of digital influencers who talk about artisanal cheeses and the dissemination of information on the network.